Empowering Rural Women in Agriculture (WIA) Through Extension Education - C.C., Godson Ibeji; O.O., Aja; C. , Uwandu (International Journal For Research In Agricultural And Food Science, 2019)
Women-in-Agriculture (WIA), a group that embodies all rural women farmers in Nigeria deserve a better appreciation and recognition of their tangible contributions to agricultural development and food security. Rural women farmers more than their men counter parts take the lead in agricultural activities, making up to 60-80 percent of labour force. It is ironical that their contributions to agricultural development are seldom noticed, they have no or minimal part to play in the decision-making process regarding agricultural policy. There has not been enough women ministers of agriculture who should have a voice to contribute in the agricultural decision making of the country which should benefit the women farmers. This paper therefore explored the role of extension education as a critical tool for empowering women-in-agriculture and emancipating them into the agenda of agricultural policy making and thereby breaking the strong-hold of poverty in their lives. The paper equally suggested that both state and federal governments should appoint more women commissioners and ministers of agriculture to help in reshaping the obnoxious traditions that negate women’s participation in agricultural policy making of this country. It finally concluded that if the millennium Development Goals’ (MDGs) target should be met and sustained, women-in-agriculture should be empowered because good training will enhance and enable them fight marginalization and subjugation of their men folk that have negated their contributions in the agricultural development agenda of the government.